Mengenal Dunia Digital : Edukasi dan Pendampingan Digital Marketing Kepada UMKM - Windyaningsih Dwi Astuti; Nugraeni, Nugraeni (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Advances in technology, the internet, and more sophisticated business management methods have led to an increase in its use by many people. Currently, technological developments have a significant impact on various aspects, including small and medium businesses. If an entrepreneur does not have expertise in the field of digital marketing, they can experience difficulties in developing their business. By using digital marketing strategies, small and medium entrepreneurs can optimize the opportunities offered by online platforms to advertise their businesses, reach more potential consumers, and compete in the global market. This service activity is aimed at small and medium entrepreneurs who are still unfamiliar with and understand the concept of digital marketing and aims to provide assistance in understanding and using technology and online marketing strategies to remain competitive and develop in today's digital era.